The Clot-Promoting Effect of Adenosine-5’-Diphosphate (ADP). II. Site of Action - Pizzuto, J; Didisheim, P; Bithell, Th. C (Thrombosis and Haemostasis, 1967)
1. ADP accelerates the rate of the “contact” phase of thromboplastin generation by a mechanism which is independent of its known effects on platelets.2. The acceleratory effect is the result of an interaction between ADP and a plasma factor which is not clearly identifiable with any generally recognized coagulation factor (i. e., factors I-XIII).